Pest categorisation of Coccus viridis - EFSA Panel on Plant Health (PLH); Antonio Vicent Civera; Paula Baptista; Anna Berlin; Elisavet Chatzivassiliou; Jaime Cubero; Nik Cunniffe; Eduardo de laPeña; Nicolas Desneux; Francesco Di Serio; Anna Filipiak; Paolo Gonthier; et al. (EFSA Journal, 2025)
Abstract The EFSA Panel on Plant Health performed a pest categorisation of Coccus viridis (Hemiptera: Coccidae), the green coffee scale, for the territory of the European Union (EU), following the commodity risk assessment of Jasminum polyanthum from Uganda, in which C. viridis was identified as a pest of possible concern to the EU. Coccus viridis is distributed in tropical and subtropical areas of the Americas, Africa, Asia and Oceania. In the EU, C. viridis occurs on the Azores and Madeira Islands (Portugal). It is a polyphagous pest, feeding on plant species belonging to more than 200 genera from 72 plant families, primarily on coffee (Coffea arabica), guava (Psidium guajava) and cacao (Theobroma cacao) plants. Hosts that are grown in the EU include Apium graveolens, Citrus spp., Eriobotrya japonica, Eucalyptus camaldulensis, Mangifera indica, Pyrus communis and some ornamental plants. Plants for planting, fruits, vegetables and cut flowers provide potential pathways for entry into the EU. Climatic conditions and availability of host plants in southern and central EU countries would allow this species to establish and spread. However, since little is known about the pest‐specific temperature requirements, and considering its tropical and subtropical origin, there is uncertainty about its ability to establish outdoors in central EU. Nevertheless, establishment could occur in greenhouses and on indoor plantings in such areas. Introduction and spread of C. viridis would likely have an economic impact in the EU, but there is uncertainty on the magnitude. This insect is not listed in Annex II of Commission Implementing Regulation (EU) 2019/2072. Phytosanitary measures are available to reduce the likelihood of entry and further spread. While the magnitude of impact in the EU is associated with uncertainty, all criteria assessed by EFSA for consideration as a potential quarantine pest are met.